Postoperative Fatigue: Clinical Applications and Associated Influencing Factors - Guo, Runjie; Wu, Shile; Gao, Wei; Zhu, Wenjun (Journal of Contemporary Medical Practice, 2025)
Postoperative fatigue (POF) refers to a widespread and common state of fatigue experienced by patients following surgery. It is typically characterized by symptoms such as weakness, lack of concentration, low mood, and sleep disturbances. This condition not only affects the patient’s postoperative recovery but may also increase the length of hospital stays, delay functional recovery, and significantly reduce quality of life. The occurrence of postoperative fatigue is related to various factors, including the type of surgery, postoperative complications, preoperative health status, and the patient’s personal characteristics (such as psychological state and underlying health conditions). Although postoperative fatigue is widely recognized in clinical settings, its specific mechanisms remain unclear. This article reviews the definition, epidemiological features, pathophysiological mechanisms, clinical manifestations, assessment methods, and clinical management strategies of postoperative fatigue. By analyzing relevant domestic and international literature, the article aims to provide clinicians with comprehensive management approaches for postoperative fatigue and discusses future research directions.